Indications of manufactured incompetence: Neopatrimonial governance and public service erosion in Indonesia's Free Nutritious Meal Program - Tegar Bimantoro; Ahmad Bagus Sasongko; Afi Kamilia (Privietlab, 2026)
Welfare policy failures in developing countries are commonly attributed to state capacity constraints. However, this study argues that in certain contexts, incompetence does not merely emerge as a systemic failure; rather, it can be actively produced as a governance strategy. This article examines the governance pathologies of Indonesia’s Free Nutritious Meal (MBG) Program (2024–2026) using a Critical Policy Analysis design, an interdisciplinary qualitative approach, and an evidence grading framework. The findings identify a structural anomaly wherein massive fiscal allocations coincide with relaxed institutional oversight. The study advances two main theoretical contributions. First, it introduces the Asymmetric Governance Paradox—a condition of inverted accountability where regular sectors face strict oversight while capital-intensive programs operate with excessive discretion. Second, it formulates the Neopatrimonial Governance Loop model, illustrating how populist narratives function as Discursive Insulation to blunt criticism, thereby facilitating Institutional Capture and the systemic reproduction of Manufactured Incompetence. Early empirical signals during the implementation phase reveal service quality deficits and institutional disruptions, confirming the operation of these mechanisms at the operational level. These findings indicate that within neopatrimonial contexts, governance failures do not necessarily reflect state failure; rather, they may function as mechanisms of power reproduction. The findings underscore the necessity of structural interventions—particularly real-time preventive audits and merit-based standards—to disrupt the reproduction of incompetence in welfare governance.